The structures of two archaeal type IV pili illuminate evolutionary relationships - Fengbin Wang (Nature Portfolio, 2020)
Archaeal type IV pili (T4P) mediate adhesion to surfaces and are receptors for hyperthermophilic archaeal viruses. Here, the authors present the cryo-EM structures of two archaeal T4P from Pyrobaculum arsenaticum and Saccharolobus solfataricus and discuss evolutionary relationships between bacterial T4P, archaeal T4P and archaeal flagellar filaments.